Daily life in the United States, 1920-1940 : how Americans lived through the "Roaring Twenties" and the Great Depression - Kyvig, David E. (Chicago : Ivan R. Dee, 2004)
Publisher description: The twenties and thirties witnessed dramatic changes in American life: increasing urbanization, technological innovation, cultural upheaval, and economic disaster. In this book, the prize-winning historian David Kyvig describes everyday life in these decades, when automobiles and home electricity became commonplace, when radio and the movies became broadly popular. The details of work life, domestic life, and leisure activities make engrossing reading and bring the era clearly into focus.
The circumstances of American life in 1920 -- Automobiles and the construction of daily life -- Electricity and the conditions of daily life -- Radio and the connecting of daily lives -- Cinema and the extension of experience -- Carrying on day by day : life's basics -- Carrying on year by year : making a life -- Conflict, crime, and catastrophe : the disruptions of daily life -- Culture for the masses : the standardizing of daily life -- Crisis : the impact of the Great Depression -- Creating the New Deal : a larger role for government in daily life -- Continuity and change : American communities at the end of the 1930s.
Includes bibliographical references (p. 305-313) and index.
Keywords: United States -- Social life and customs -- 1918-1945.; United States -- Social conditions -- 1918-1932.; United States -- Social conditions -- 1933-1945.; Nineteen twenties; Nineteen thirties